Clinical Specimens are the Pool of Multidrug- resistant Pseudomonas aeruginosa Harbouring oprL and toxA Virulence Genes: Findings from a Tertiary Hospital of Nepal - Yamuna Chand; Sujan Khadka; Sanjeep Sapkota; Suprina Sharma; Santosh Khanal; Alina Thapa; Binod Rayamajhee; Dhruba Kumar Khadka; Om Prakash Panta; Dipendra Shrestha; Pramod Poudel (Emergency Medicine International)
The multidrug- or extensively drug-resistant (MDR/XDR) Pseudomonas aeruginosa carrying some virulence genes has become a global public health threat. However, in Nepal, there is no existing report showing the prevalence of oprL and toxA virulence genes among the clinical isolates of P. aeruginosa. Therefore, this study was conducted for the first time in the country to detect the virulence genes (oprL and toxA) and antibiotic susceptibility pattern of P. aeruginosa. A total of 7,898 clinical specimens were investigated following the standard microbiological procedures. The antibiotic susceptibility testing was examined by the modified disc diffusion method, and virulence genes oprL and toxA of P. aeruginosa were assessed using multiplex PCR. Among the analyzed specimens, 87 isolates were identified to be P. aeruginosa of which 38 (43.68%) isolates were reported as MDR. A higher ratio of P. aeruginosa was detected from urine samples 40 (45.98%), outpatients’ specimens 63 (72.4%), and in patients of the age group of 60–79 years 36 (41.37%). P. aeruginosa was more prevalent in males 56 (64.36%) than in female patients 31 (35.63%). Polymyxin (83.90%) was the most effective antibiotic. P. aeruginosa (100%) isolates harboured the oprL gene, while 95.4% of isolates were positive for the toxA gene. Identification of virulence genes such as oprL and toxA carrying isolates along with the multidrug resistance warrants the need for strategic interventions to prevent the emergence and spread of antimicrobial resistance (AMR). The findings could assist in increasing awareness about antibiotic resistance and suggest the judicious prescription of antibiotics to treat the patients in clinical settings of Nepal.